Risk factors and bacterial spectrum postoperative infections after esophageal tumor surgery in patients aged ≥60 years - Li, Dan; Lin, Mingzhu; Gu, Huawei (Frontiers in Oncology, 2025)
PurposePatients undergoing esophageal tumor surgery (ETS) are at increased risk of postoperative infections (PI), particularly those aged ≥60 years. To improve perioperative safety and outcomes in this population, this study aimed to investigate the bacterial spectrum and identify risk factors associated with PI following ETS.MethodsA total of 747 patients who underwent radical esophagectomy between January and December 2021 were included in this retrospective analysis. Clinical data, including demographic characteristics, comorbidities, surgery-related variables, and laboratory indicators, were collected and analyzed.ResultsPreoperative and intraoperative risk factors for PI were evaluated using univariate and multivariate logistic regression analyses. The overall incidence of PI was 29.6% (221/747). Smoking, prolonged surgical duration, and elevated postoperative blood glucose levels were identified as independent risk factors for postoperative infection.ConclusionElderly patients undergoing ETS are at considerable risk for PI, particularly those with modifiable risk factors such as smoking and hyperglycemia. Identification of high-risk individuals and implementation of targeted preventive strategies may reduce the incidence of postoperative infections and improve surgical outcomes.